IL-10-producing T cells and their dual functions. (August 2019) - Bedke, Tanja; Muscate, Franziska; Soukou, Shiwa; Gagliani, Nicola; Huber, Samuel
Abstract: Interleukin (IL)-10 is considered a prototypical anti-inflammatory cytokine, which significantly contributes to the maintenance and reestablishment of immune homeostasis. However, this classical view fails to fully describe the pleiotropic roles of IL-10. Indeed, IL-10 can also promote immune responses, e.g. by supporting B-cell and CD8 + T-cell activation. The reasons for these seemingly opposing functions are unclear to a large extent. Recent and previous studies suggest that the cellular source and the microenvironment impact the function of IL-10. However, studies addressing the mechanisms which determine whether IL-10 promotes inflammation or controls it have just begun. This review first summarizes the recent findings on the heterogeneity of IL-10 producing T cells and their impact on the target cells. Finally, we will propose two possible explanations for the dual functions of IL-10.